THE DALAT UNIVERSITY’S ENTREPRENEURSHIP FACILITATION CENTER – PROMOTING INNOVATION, INCUBATING ENTREPRENEURSHIP - Trương Thị Ngọc Thuyên (Tạp chí Khoa học Đại học Đà Lạt)
This non-scholarly article introduces The Entrepreneurship Facilitation Center of Dalat University.